Teaching Einsteinian physics at schools: part 3, review of research outcomes. (22nd September 2017) - Kaur, Tejinder; Blair, David; Moschilla, John; Stannard, Warren; Zadnik, Marjan
Abstract: This paper reviews research results obtained from Einsteinian physics programs run by different instructors with Years 6, 9, 10 and 11 students using the models and analogies described in parts 1 and 2. The research aimed to determine whether it is possible to teach Einsteinian physics and to measure the changes in student attitudes to physics engendered by introducing the modern concepts that underpin technology today. Results showed that students easily coped with the concepts of Einsteinian physics, and considered that they were not too young for the material presented. Importantly, in all groups, girls improved their attitude to physics considerably more than the boys, generally achieving near parity with the boys.